Nash bargaining and the wage consequences of educational mismatches - Joop Hartog; Michael Sattinger (Institute for the Study of Labor (IZA), 2012)
The paper provides a theoretical foundation for the empirical regularities observed in estimations of wage consequences of overeducation and undereducation. Workers with more education than required for their jobs are observed to suffer wage penalties relative to workers with the same education in jobs that only require their educational level. Similarly, workers with less education than required for their jobs earn wage rewards. These departures from the Mincer human capital earnings function can be explained by Nash bargaining between workers and employers. Under fairly mild assumptions, Nash bargaining predicts a wage penalty for overeducation and a wage reward for undereducation, and further predicts that the wage penalty will exceed the wage reward. This paper reviews the established empirical regularities and then provides Nash bargaining results that explain these regularities.
Keywords: J31; J24; C78; C51; 330; overeducation; undereducation; Nash bargaining; qualitative mismatches; Mincer earnings function; wages; Lohn; Unterbeschäftigung; Bildungsertrag; Lohnverhandlungen; Nash-Gleichgewicht; Theorie